A person-centred and thriving-promoting intervention in nursing homes - study protocol for the U-Age nursing home multi-centre, non-equivalent controlled group before-after trial. Issue 1 (December 2017) - Edvardsson, David; Sjögren, Karin; Lood, Qarin; Bergland, Ådel; Kirkevold, Marit; Sandman, Per-Olof
Abstract Background The literature suggests that person-centred care can contribute to quality of life and wellbeing of nursing home residents, relatives and staff. However, there is sparse research evidence on how person-centred care can be operationalised and implemented in practice, and the extent to which it may promote wellbeing and satisfaction. Therefore, the U-Age nursing home study was initiated to deepen the understanding of how to integrate person-centred care into daily practice and to explore the effects and meanings of this. Methods The study aims to evaluate effects and meanings of a person-centred and thriving-promoting intervention in nursing homes through a multi-centre, non-equivalent controlled group before-after trial design. Three nursing homes across three international sites have been allocated to a person-centred and thriving-promoting intervention group, and three nursing homes have been allocated to an inert control group. Staff at intervention sites will participate in a 12-month interactive educational programme that operationalises thriving-promoting and person-centred care three dimensions: 1) Doing a little extra, 2) Developing a caring environment, and 3) Assessing and meeting highly prioritised psychosocial needs. A pedagogical framework will guide the intervention. The primary study endpoints are; residents' thriving, relatives' satisfaction with care and staff job satisfaction. Secondary endpoints are; resident, relative and staff experiences of the caring environment, relatives' experience of visiting their relative and the nursing home, as well as staff stress of conscience and perceived person-centredness of care. Data on study endpoints will be collected pre-intervention, post-intervention, and at a six-month follow up. Interviews will be conducted with relatives and staff to explore experiences and meanings of the intervention. Discussion The study is expected to provide evidence that can inform further research, policy and practice development on if and how person-centred care may improve wellbeing, thriving and satisfaction for people who reside in, visit or work in nursing homes. The combination of quantitative and qualitative data will illuminate the operationalisation, effects and meaning of person-centred and thriving-promoting care. Trial registration The trial was registered at ClinicalTrials.gov March 19, 2016, identifierNCT02714452 .